The cause of anxiety among ESL learners: Is it examination, negative feedback or communication / Mohd Ismail Azizi Md Ishak - Md Ishak, Mohd Ismail Azizi (Faculty of Education, 2014)
This research journal looks at the issue of anxiety among learners of English as a second language (ESL) or for some they say that English is a foreign language to them. The participants were form four school students. The research focused onto secondary school students as we want to see the perspective of school students as how they see and perceive their anxiety level in learning the English language in school. The research is interested to view what the students perceive as the skill which caused anxiety the most, is it reading, writing or listening and speaking as well as to determine what actually cause anxiety the most in students, is it ‘‘examination, teacher's feedbacks or communication”. The instrument used is a modified version of Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, E. K., Horwitz, M. B., & Cope, J. (1986), called Second Language Classroom Anxiety Scale (SLCAS). The results indicated that nearly all of the students viewed writing skill as the most worried aspect in learning English. Also, test taking anxiety is found to be the main item that causes anxiety the most to the students. The findings then lead to several recommendations on how to help reduce the effect of anxiety to ESL learners and English language learner, (ELL). This research will hopefully help the learners to get a better grasp of what they can do to reduce their anxiety level in learning English.